Incidence and outcomes of rare T cell lymphomas from the T Cell Project: hepatosplenic, enteropathy associated and peripheral gamma delta T cell lymphomas. Issue 2 (25th November 2019) - Foss, Francine M.; Horwitz, Steven M.; Civallero, Monica; Bellei, Monica; Marcheselli, Luigi; Kim, Won Seog; Cabrera, Maria E.; Dlouhy, Ivan; Nagler, Arnon; Advani, Ranjana H.; Pesce, Emanuela A.; Ko, Young‐Hyeh; et al.
Abstract: The T Cell Project was the largest prospective trial to explore the incidence, treatment patterns, and outcomes for T cell lymphomas. The rare subtypes of T cell lymphomas, including hepatosplenic T cell lymphoma (HSTCL), enteropathy associated T cell lymphoma (EATL), and peripheral gamma delta T cell lymphomas (PGDTCLs) are poorly represented in most studies and there is little data regarding treatment patterns. We report results from 115 patients with hepatosplenic (n = 31), enteropathy associated (n = 65), and PGDTCLs (n = 19). While anthracycline regimens were most commonly used as first line therapy, response rates ranged from 20%‐40% and were suboptimal for all groups. Autologous stem cell transplantation was performed as a consolidation in first remission in a small number of patients (33% of HSTCL, 7% of EATL, and 12% of PGDTCL), and four patients with HSTCL underwent allogeneic stem cell transplantation in first remission. The progression free survival at 3 years ranged from 28%‐40% for these rare subtypes, and the overall survival at 3 years was most favorable for PGDTCL (70%). These data highlight the need for novel treatment approaches for rare subtypes of T cell lymphomas and for their inclusion in clinical trials.